Polyurethane composition and composite material containing same
By adding phase change heat-absorbing material to the polyurethane composition, the contradiction between operating period and holding time in the HPRTM process is solved, and the operation period is extended and the holding time is shortened, thereby improving production efficiency and product performance.
Patent Information
- Application Number
- CN202411798338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
In the high-pressure resin transfer molding (HPRTM) process, there is a contradiction between the operating period of existing polyurethane resins and the product maturation time. Although the application of thermally sensitive catalysts solves some problems, when increasing the catalyst content or increasing the mold temperature to shorten the holding time, the operating period will be shorter, affecting the product's infiltration and the production of large products.
By adding at least one phase change heat-absorbing material to the polyurethane composition, the material undergoes phase change heat-absorbing at a specific temperature, thereby maintaining the combined material temperature when it is lower than the heat-sensitive catalyst activation temperature, prolonging the operation period, and reacting faster after reaching the catalyst activation temperature and shortening the pressure holding time.
It achieves shortening the pressure holding time, improving production efficiency, ensuring good product wetting and appearance performance, and adapting to different working conditions while extending the operating period.
Smart Images

Figure BDA0005177378650000091 
Figure BDA0005177378650000092 
Figure BDA0005177378650000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane compositions, and in particular to a polyurethane composition for preparing a composite material. Background Art
[0002] Polyurethane composite materials are currently widely used in many fields, among which polyurethane is characterized by its high activity and wide adjustable performance range. In industrial production, how to improve production efficiency and product performance is a long-term topic. Improving production efficiency means reducing costs. High-pressure resin transfer molding (HPRTM) is a composite material preparation method that has emerged in recent years. The preform of the reinforced material prepared in advance is placed in the mold and vacuumed, and then the resin is injected into the mold for pressure molding. The characteristic of the HPRTM process is high production efficiency, so it is favored by many manufacturers. The requirement of HPRTM for resin materials is that the faster the reaction, the better, under the premise of sufficient operating period.
[0003] At present, the resins used in the HPRTM process on the market are mainly epoxy resin and polyurethane resin. Among them, polyurethane resin generally uses thermosensitive catalysts or reaction inhibitors to prolong the reaction time of the two components to ensure good infiltration of the reinforcing materials during the injection of the resin into the mold. After the main raw materials of the formula are confirmed, there is a contradiction between the operation period and the product maturation time. The application of thermosensitive catalysts has solved this contradiction to a certain extent, but there is also a problem that when the amount of catalyst added is small, the operation period is long but a longer pressure holding time is required, and the operation period will be shorter when the amount of catalyst added is large; at the same time, when large-scale product production is carried out, when the injection flow rate is constant, the resin flow time will be extended, and when the operation period is insufficient, the product is prone to defects such as poor appearance and color difference.
[0004] Chinese patent CN106232671B discloses a composite material and method for obtaining a fiber composite component by impregnating fibers with a polyurethane reactive resin mixture. The main feature of the invention is the use of organic NCO prepolymers, polyol components and thermosensitive catalysts to achieve a long operating period. However, if the holding time is to be further reduced, the reaction activity is increased by increasing the catalyst content or raising the mold temperature, the operating period will be shortened, affecting the impregnation of the product and the production of large products. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the purpose of the present invention is to provide a polyurethane composition and a composite material containing the same, which can further reduce the holding time and improve the production efficiency while extending the operation period.
[0006] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a polyurethane composition, which comprises the following components:
[0008] a) isocyanate component;
[0009] b) an isocyanate-reactive component, the isocyanate-reactive component comprising:
[0010] b1) polyols;
[0011] b2) at least one phase change endothermic material;
[0012] b3) optional heat-sensitive catalyst;
[0013] b4) optional additives;
[0014] The phase-change heat-absorbing material undergoes phase change at 35-100° C. and absorbs heat.
[0015] In some specific embodiments, based on the total mass of the isocyanate reactive component as 100%,
[0016] The polyol is used in an amount of 50 to 90%;
[0017] The amount of the phase change endothermic material is 3 to 10%;
[0018] The amount of the heat-sensitive catalyst is 0 to 0.7%;
[0019] The dosage of the additive is 0-40%.
[0020] In some preferred embodiments, based on the total mass of the isocyanate-reactive component as 100%,
[0021] The amount of the polyol is 65-75%;
[0022] The amount of the phase change endothermic material is 5-8%;
[0023] The amount of the heat-sensitive catalyst is 0.2-0.5%;
[0024] The dosage of the additive is 10-30%.
[0025] In some embodiments, the component a) is selected from isocyanate monomers and / or polyisocyanates; the isocyanate monomers are selected from one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate;
[0026] The polyisocyanate is selected from polyphenyl polymethylene polyisocyanate.
[0027] In some embodiments, in the component b), the activation temperature of the thermosensitive catalyst is not lower than the phase change temperature of the phase change endothermic material;
[0028] Among them, the activation temperature of the thermosensitive catalyst is not lower than the phase change temperature of the phase change endothermic material; in some preferred embodiments, the thermosensitive catalyst is selected from one or more of a closed amine catalyst, a closed amine catalyst and a highly sterically hindered organic metal catalyst.
[0029] In some specific embodiments, the blocked amine catalyst is selected from triethylenediamine formate, triethylenediamine 2-ethylhexanoic acid or Evonik POLYCAT SA series;
[0030] The highly sterically hindered organic metal catalyst is selected from Maitu UL-29 or Maitu UL-32.
[0031] In some embodiments, in component b1), the polyol is selected from small molecule polyols and / or macromolecular polyols;
[0032] The small molecule polyol is selected from one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentyl glycol, glycerol, and trimethylolpropane;
[0033] The macromolecular polyol is selected from one or more of polyether polyols, polyether polyols, polycarbonate polyols, and polyacrylate polyols.
[0034] In some embodiments, in component b2), the phase-change endothermic material is selected from one or more of paraffin, PEG-1000, PEG-2000, PEG-4000 and stearic acid.
[0035] In some embodiments, in component b4), the additive is selected from one or more of a flame retardant, a dye, a dehumidifier, a defoamer, an antioxidant, an antistatic agent, a dispersant, an internal release agent, and a filler.
[0036] In a second aspect, the present invention provides a polyurethane composite material, the composite material comprising a reinforcing material and the polyurethane composition described above.
[0037] In some embodiments, the reinforcing material is selected from one or more of glass fiber fabric, carbon nanotubes, carbon fibers, polyester fibers, aromatic polyamide fibers, nylon fibers, basalt fibers, boron fibers, silicon carbide fibers, asbestos fibers, whiskers, and hard particles.
[0038] The above technical solution has the following technical effects:
[0039] The polyurethane composition provided by the present invention can undergo phase change and endothermic absorption at a specific temperature by adding at least one phase change endothermic material, thereby maintaining the temperature of the composite material below the activation temperature of the heat-sensitive catalyst for a certain period of time. In this way, increasing the content of the heat-sensitive catalyst or raising the mold temperature can make the reaction faster after reaching the activation temperature of the catalyst, shorten the pressure holding time, and the operation period will not be greatly affected.
[0040] The polyurethane composition provided by the present invention can obtain polyurethane composite materials with different operating periods by combining different types of phase-change heat-absorbing materials and heat-sensitive catalysts to adapt to different working conditions. DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0042] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0043] The polyurethane composition provided by the present invention comprises the following components:
[0044] a) isocyanate component;
[0045] b) a reactive component that reacts with the isocyanate component, the isocyanate reactive component comprising:
[0046] b1) polyols;
[0047] b2) at least one phase change endothermic material;
[0048] b3) optional heat-sensitive catalyst;
[0049] b4) optional additives;
[0050] The phase-change heat-absorbing material undergoes phase change at 35-100° C. and absorbs heat.
[0051] In the polyurethane composition provided by the present invention, the isocyanate component is a class of compounds containing isocyanate groups in the molecular structure, which can be isocyanate monomers, polyisocyanates or a mixture of the two. The isocyanate monomers can be selected from commonly used ones such as diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate, etc., and the polyisocyanate can be selected from polyphenyl polymethylene polyisocyanates.
[0052] The polyurethane composition provided by the present invention adds at least one phase-change heat-absorbing material, so that the material can undergo phase-change heat absorption at a specific temperature, so that the temperature of the composite material is maintained for a certain period of time below the activation temperature of the heat-sensitive catalyst. Increasing the content of the heat-sensitive catalyst or raising the mold temperature in this way can make the reaction faster after reaching the activation temperature of the catalyst, shorten the pressure holding time, and the operating period will not be greatly affected. The present invention obtains polyurethane composite materials with different operating periods by combining different types of phase-change heat-absorbing materials and heat-sensitive catalysts, which can adapt to different working conditions.
[0053] In the polyurethane composition provided by the present invention, the polyol b1) in the isocyanate reactive component is selected from small molecule polyols and / or macromolecular polyols, and the small molecule polyol is selected from one or more of ethylene glycol, propylene glycol, 1,4-butanediol, and pentaerythritol. The small molecule alcohol can play the role of extending the polymer molecule chain, crosslinking, and increasing the molecular weight. Among them, the macromolecular polyol is selected from one or more of polyether polyols, polyether polyols, polycarbonate polyols, and polyacrylate polyols; preferably, polyether polyols are used, and polyether polyols are a class of compounds obtained by polymerization with polyols as initiators and alkylene oxides as monomers, wherein the initiators include water, ethylene glycol, propylene glycol, glycerol, trimethylolpropane, triethanolamine, pentaerythritol, ethylenediamine, toluenediamine, xylitol, sorbitol, mannitol, sucrose, etc., and a suitable initiator is selected according to the required functionality, and the molecular weight can be controlled to obtain polymer polyols with different hydroxyl values.
[0054] The polyurethane composition provided by the present invention may contain or not contain a thermosensitive catalyst, specifically, contain zero, one or more thermosensitive catalysts; at the same time, the polyurethane composition provided by the present invention may contain or not contain additives, specifically, contain zero, one or more additives.
[0055] In some specific embodiments, based on the total mass of the isocyanate reactive component as 100%,
[0056] The polyol is used in an amount of 40 to 90%;
[0057] The amount of the phase change endothermic material is 3 to 10%;
[0058] The amount of the heat-sensitive catalyst is 0 to 0.7%;
[0059] The dosage of the additive is 0-30%.
[0060] In some preferred embodiments, based on the total mass of the isocyanate reactive component as 100%,
[0061] The amount of the polyol is 55-75%;
[0062] The amount of the phase change endothermic material is 5-8%;
[0063] The amount of the heat-sensitive catalyst is 0.2-0.5%;
[0064] The dosage of the additive is 10-20%.
[0065] The phase-change endothermic material mentioned in the present invention refers to a material that changes its state and provides latent heat when the temperature remains unchanged. The phase-change endothermic material absorbs or releases a large amount of latent heat when a phase change occurs. In the polyurethane composition provided by the present invention, the phase-change endothermic material is initially a solid substance in the isocyanate reactive component. When heated in the mold to reach its phase change temperature, it can be transformed into a liquid state and absorb a large amount of heat so that the temperature of the reaction mixture is maintained at its phase change temperature for a period of time. After the phase change is completed, the temperature continues to rise, thus extending the operation period. During the operation period, the reaction degree of the reaction mixture is very low, and the reinforcing material can be fully infiltrated, so that the appearance and performance of the product are significantly improved, and it can adapt to more production conditions.
[0066] In some specific embodiments, the phase change endothermic material undergoes a phase change at 35-100°C and absorbs heat, and can be specifically selected from one or more of paraffin, PEG-1000, PEG-2000 (phase change temperature is 51.0°C), PEG-4000 (phase change temperature is 59.7°C) and stearic acid (phase change temperature is 70.0°C).
[0067] In the polyurethane composition provided by the present invention, the thermosensitive catalyst refers to a type of catalyst having obvious catalytic activity at a specific temperature or temperature range, examples of which include but are not limited to one or more of blocked amine catalysts, blocked amidine catalysts and highly sterically hindered organic metal catalysts; more specific examples include but are not limited to formate or phenolate or isooctanoate of dimethylcyclohexylamine, dioctyltin dithiol, bis(dimethylaminoethyl) ether derivatives, etc., commercial products include WANALYST KC110 (activation temperature of 60°C) and WANALYST KC101 produced by Wanhua Chemical and BICAT 2536 (activation temperature of 72°C) produced by Leading Chemical.
[0068] The blocked amine catalyst is selected from triethylenediamine formate, triethylenediamine 2-ethylhexanoic acid or Evonik POLYCAT SA series; the highly sterically hindered organic metal catalyst is selected from Maitu UL-29 and Maitu UL-32.
[0069] In some specific embodiments, if component b contains a thermosensitive catalyst, the activation temperature of the thermosensitive catalyst should not be lower than the phase change temperature of the phase change material to prevent the catalyst from catalyzing before the phase change material takes effect.
[0070] In some specific embodiments, in order to meet other requirements of the product such as flame retardancy, color, defoaming, etc., the following additives can be added, for example, one or more of flame retardants, dyes, dewatering agents, defoaming agents, antioxidants, antistatic agents, dispersants, internal release agents and fillers.
[0071] The present invention also provides a polyurethane composite material, which comprises a reinforcing material and the polyurethane composition.
[0072] In some specific embodiments, the reinforcing material is selected from one or more of glass fiber fabric, carbon nanotubes, carbon fibers, polyester fibers, aromatic polyamide fibers, nylon fibers, basalt fibers, boron fibers, silicon carbide fibers, asbestos fibers, whiskers and hard particles.
[0073] When preparing the polyurethane composite material provided by the present invention, conventional techniques in the art can be used, such as the HPRTM process; specifically, the reinforcing material is preformed so that the fiber maintains a predetermined position when placed in the mold, the mold is evacuated after the mold is closed, and then the polyurethane composition is injected into the mold, and the temperature of the mold is controlled at 60 to 120° C. to start the reaction. When the temperature rises to the phase change temperature of the phase change endothermic material, the material undergoes a phase change while the temperature of the reaction mixture remains unchanged. After the phase change is completely completed, the temperature continues to rise. After reaching the activation temperature of the thermosensitive catalyst, the reaction proceeds rapidly. After the resin is cured, the mold is opened and the product is taken out.
[0074] In the traditional or conventional formula in which only a heat-sensitive catalyst is added, after being injected into the mold, it is difficult to avoid premature heating of the resin layer close to the mold and reaction, resulting in the phenomenon of resin deficiency. However, after adding the phase change endothermic material to the formula of the present invention, the heating rate can be significantly reduced, thereby delaying the start time of the reaction, improving the product appearance, and strengthening the resin's infiltration into the reinforcing material, further improving the performance of the composite material.
[0075] The polyurethane composite material provided by the present invention adds a phase change endothermic material whose phase change temperature is lower than the activation temperature of a heat-sensitive catalyst, so that before the composition is injected into a mold for molding and curing, it can be kept at or below the phase change temperature of the phase change endothermic material for a certain time, so that the composition can fully infiltrate the reinforcing material. By adjusting the amount of the phase change endothermic material added, the holding time at the phase change temperature can be adjusted, so as to obtain composite materials with different operating periods. Even by adding multiple phase change materials, multiple temperatures can be kept for a certain time, and the flexibility is very high, so that the operating period of the reactants is not significantly affected under the condition of increasing the content of the heat-sensitive catalyst or raising the mold temperature.
[0076] The present invention is further described below by means of specific examples, but it should not be understood that the present invention is limited thereto.
[0077] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents used without specifying the manufacturer are all conventional reagents available in the art.
[0078] The following implementations are tested using the following methods:
[0079] The test standards for tensile strength, tensile modulus and flexural modulus are: DIN ISO 527.
[0080] Source of raw materials:
[0081] Polyether polyol 1: obtained by polymerization of propylene oxide with glycerol as an initiator, with a hydroxyl value of 600 mg KOH / g and a functionality of 3;
[0082] Polyether polyol 2: obtained by polymerization with propylene oxide using glycerol as an initiator, with a hydroxyl value of 400 mg KOH / g and a functionality of 3;
[0083] Polymer polyol 3: obtained by polymerization with propylene oxide using pentaerythritol as an initiator, with a hydroxyl value of 800 mgKOH / g and a functionality of 4;
[0084] Polymer polyol 4: obtained by polymerization with propylene oxide using sucrose as an initiator, with a hydroxyl value of 60 mg KOH / g and a functionality of 8;
[0085] Phase change endothermic materials: PEG-2000, PEG-4000, stearic acid;
[0086] Additives: flame retardant A710, Shanghai Wandao Chemical Co., Ltd.;
[0087] Thermosensitive catalyst: KC110, Wanhua Chemical;
[0088] Thermosensitive catalyst: BICAT 2536, Leading Chemical;
[0089] Dispersant: BYK-9909, BYK Chemical;
[0090] Internal release agent: HB-650D, TECHNICK PRODUCTS;
[0091] Isocyanate: WANNATE PM200, NCO content 31.2wt%, Wanhua Chemical;
[0092] Fiberglass cloth: EWR400, China Jushi Co., Ltd.
[0093] The amounts of the components of the polyurethane composition in the following embodiments are added according to Table 1-2:
[0094] Table 1
[0095]
[0096]
[0097] Note: “ / ” in the above table means that the component is not contained.
[0098] Table 2
[0099]
[0100]
[0101] Note: “ / ” in the above table means that the component is not contained.
[0102] The polyurethane composite material is prepared by the following method:
[0103] The glass fiber cloth is preformed, and the preformed fiber cloth is placed in a mold. After the mold is closed, the mold is evacuated, and then the above-mentioned polyurethane composition is injected into the mold. The temperature of the mold is controlled at 60-120°C for curing and molding. After completion, the mold is opened and the product is taken out.
[0104] The specific preparation conditions and properties of the obtained products are shown in Table 3-4 below:
[0105] Table 3
[0106]
[0107]
[0108] Table 4
[0109]
[0110] From the above results, it can be seen that the polyurethane composition provided by the present invention is added with at least one phase change endothermic material, and the effect of extending the window period can be achieved even without adding a thermosensitive catalyst; at the same time, after adding the phase change material, the viscosity of the reaction mixture increases to 5000cP, the reaction time becomes longer, that is, the operation time becomes longer; the interlaminar shear strength is further improved, the wetting effect is better, the appearance of the composite material product is better, the mechanical strength is higher, and a shorter holding time can be achieved at a high mold temperature.
[0111] Judging from the comparative results, if the activation temperature of the thermosensitive catalyst added to the polyurethane composition is lower than the phase change temperature of the phase change material, the material's effect of extending the window period and improving the wetting will be affected. This is because premature activation of the catalyst will make the reaction more intense below the phase change temperature of the phase change material.
Claims
1. A polyurethane composition, characterized in that The polyurethane composition comprises the following components: a) isocyanate component; b) an isocyanate-reactive component, the isocyanate-reactive component comprising: b1) polyols; b2) at least one phase change endothermic material; b3) optional heat-sensitive catalyst; b4) optional additives; The phase-change heat-absorbing material undergoes phase change at 35-100° C. and absorbs heat.
2. The polyurethane composition according to claim 1, characterized in that Taking the total mass of component b) as 100%, The polyol is used in an amount of 50 to 90%; The amount of the phase change endothermic material is 3 to 10%; The amount of the heat-sensitive catalyst is 0 to 0.7%; The dosage of the additive is 0-40%.
3. The polyurethane composition according to claim 2, characterized in that Taking the total mass of component b) as 100%, The amount of the polyol is 65-75%; The amount of the phase change endothermic material is 5-8%; The amount of the heat-sensitive catalyst is 0.2-0.5%; The dosage of the additive is 10-30%.
4. The polyurethane composition according to any one of claims 1 to 3, characterized in that The component a) is selected from isocyanate monomers and / or polyisocyanates; The isocyanate monomer is selected from one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate; The polyisocyanate is selected from polyphenyl polymethylene polyisocyanate.
5. The polyurethane composition according to any one of claims 1 to 4, characterized in that In the component b), the activation temperature of the thermosensitive catalyst is not lower than the phase change temperature of the phase change endothermic material; Preferably, the thermosensitive catalyst is selected from one or more of a blocked amine catalyst, a blocked amidate catalyst and a highly sterically hindered organic metal catalyst; More preferably, the blocked amine catalyst is selected from triethylenediamine formate, triethylenediamine 2-ethylhexanoic acid or Evonik POLYCAT SA series; The highly sterically hindered organic metal catalyst is selected from Maitu UL-29 or Maitu UL-32.
6. The polyurethane composition according to claim 5, characterized in that In component b1), the polyol is selected from small molecule polyols and / or macromolecular polyols; The small molecule polyol is selected from one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentyl glycol, glycerol, and trimethylolpropane; The macromolecular polyol is selected from one or more of polyether polyols, polyether polyols, polycarbonate polyols, and polyacrylate polyols.
7. The polyurethane composition according to any one of claims 1 to 6, characterized in that In component b2), the phase-change endothermic material is selected from one or more of paraffin, PEG-1000, PEG-2000, PEG-4000 and stearic acid.
8. The polyurethane composition according to claim 7, characterized in that In component b4), the additive is selected from one or more of flame retardants, dyes, dehumidifiers, defoamers, antioxidants, antistatic agents, dispersants, internal mold release agents and fillers.
9. A polyurethane composite material, characterized in that: The composite material comprises a reinforcing material and the polyurethane composition according to any one of claims 1 to 8.
10. The polyurethane composite material according to claim 9, characterized in that: The reinforcing material is selected from one or more of glass fiber fabric, carbon nanotube, carbon fiber, polyester fiber, aromatic polyamide fiber, nylon fiber, basalt fiber, boron fiber, silicon carbide fiber, asbestos fiber, whisker and hard particles.
Citation Information
Patent Citations
Composite fiber components and their manufacturing
CN106232671B
Vibration-damping urethane resin composition, vibration-damping molded urethane resin object, and method for forming said molded object
CN106795265A
Polyurethane composite material and preparation method thereof
CN111019089A
Polyurethane phase-change composition and method of manufacture thereof
CN111100602A
Phase-change cooling organic reinforcing material as well as preparation formula and preparation method thereof
CN118978662A